Islamic Guidance and Counseling to Foster Gratitude in Boarding High School Students - Saputra, Muhammad Ivan Dwi; Naqiyah, Najlatun; Setiawati, Denok; Wiyono, Bambang Dibyo; Ilhamuddin, Muhammad Farid; Habsy, Bakhrudin All (Kuras Institute, 2025)
This study investigates the application of Islamic guidance and counseling to foster gratitude among students at Madrasah Aliyah (Islamic senior high school) Syekh Abdul Qodir Al-Jailani, Probolinggo. Using a quasi-experimental design with a one-group pretest-posttest approach, the study assessed gratitude levels before and after intervention. The gratitude scale, developed based on aspects of personal and transpersonal gratitude, was administered to a purposive sample of 229 students. Data analysis using a paired sample t-test revealed a significant increase in students' gratitude scores post-intervention (Sig. < 0.05). The intervention involved delivering materials on gratitude, positive perspective (khusnudzon), and appreciation, aligning with Islamic principles to promote emotional resilience, spiritual growth, and prosocial behavior. The findings suggest that integrating gratitude into Islamic counseling not only enhances emotional stability but also strengthens students' social relationships and spiritual well-being. For counselors, the study underscores the importance of culturally and spiritually sensitive approaches, particularly in Islamic settings, to address students' psychosocial and spiritual needs. The results imply that incorporating practices like reflection, prayer, and empathy into counseling can create a supportive framework for fostering gratitude as a sustainable habit, contributing to students' holistic development. This approach provides a model for counselors to align therapeutic interventions with clients' cultural and spiritual values, promoting resilience and overall mental health.